Structural behavior of a metallic truss under progressive damage. (15th March 2016) - De Biagi, Valerio
Abstract: Modern requirements on constructions impose that proper design strategies must be adopted in order to obtain a robust structure: in this sense, consequence-based design focuses the attention on the structural response to damage. The behavior of statically indeterminate structural systems under damage is nonlinear because the load paths intertwine each other, even if each component behaves linearly. The paper aims both to highlight the behavior of a metallic truss under progressive damage and to define a possible strategy for designing a truss that is able to sustain damage acting at random on one of its elements. Structural complexity is used as a leading parameter. Following the results of a parametric analysis, it emerges that, as much as the Normalized Structural Complexity Index increases, the efficacy of the load paths is spread such that the impact of random damage decreases, making the approach feasible.